Development and applications of sialoglycan-recognizing probes (SGRPs) with defined specificities: exploring the dynamic mammalian sialoglycome. (4th August 2022) - Srivastava, Saurabh; Verhagen, Andrea; Sasmal, Aniruddha; Wasik, Brian R; Diaz, Sandra; Yu, Hai; Bensing, Barbara A; Khan, Naazneen; Khedri, Zahra; Secrest, Patrick; Sullam, Paul; Varki, Nissi; et al.
Abstract: Glycans that are abundantly displayed on vertebrate cell surface and secreted molecules are often capped with terminal sialic acids (Sias). These diverse 9-carbon-backbone monosaccharides are involved in numerous intrinsic biological processes. They also interact with commensals and pathogens, while undergoing dynamic changes in time and space, often influenced by environmental conditions. However, most of this sialoglycan complexity and variation remains poorly characterized by conventional techniques, which often tend to destroy or overlook crucial aspects of Sia diversity and/or fail to elucidate native structures in biological systems, i.e. in the intact sialome. To date, in situ detection and analysis of sialoglycans has largely relied on the use of plant lectins, sialidases, or antibodies, whose preferences (with certain exceptions) are limited and/or uncertain. We took advantage of naturally evolved microbial molecules (bacterial adhesins, toxin subunits, and viral hemagglutinin-esterases) that recognize sialoglycans with defined specificity to delineate 9 classes of sialoglycan recognizing probes (SGRPs: SGRP1–SGRP9) that can be used to explore mammalian sialome changes in a simple and systematic manner, using techniques common in most laboratories. SGRP candidates with specificity defined by sialoglycan microarray studies were engineered as tagged probes, each with a corresponding nonbinding mutant probe as a simple and reliable negative control. The optimized panel of SGRPs can be used in methods commonly available in most bioscience labs, such as ELISA, western blot, flow cytometry, and histochemistry. To demonstrate the utility of this approach, we provide examples of sialoglycome differences in tissues from C57BL/6 wild-type mice and human-like Cmah −/− mice.